Bercermin pada Penanggalan Masehi - Rusdin Muhalling (Al-'Adl, 2008)
So far the system of determining the beginning of the month of Qamariyah for Muslims, has not been able to satisfy because there are still differences of perception in determining the beginning and the end of Ramadan and Dhul-Hijjah. Because of this problem, "concerning obligatory 'ain" for every Muslim, that is the obligation to run fast and hajj.Unlike the timing of prayers and the direction of the Qiblah that everyone seems to agree on, the early determination of this month is a disputed issue of the "way" used. One side is using with "Ru'yat", while on the other side with "Haisab". So the problem of determining the beginning and the end of the month, especially the months associated with fasting and hajj, has always been a sensitive issue and very worried by the government, because there is often a dispute among people, while the community is only due to different days in starting and ending the fasting Ramadan .